Answer intelligence : raise your AQ - Glibkowski, Brian (Emerald Publishing, 2021)
In a business world and society focused upon questions, there has been an underappreciation of answers in capturing our attention, imagination and critical examination. In a complex and fast-moving world, Answer Intelligence (AQ) is our ability to provide elevated answers to emotionally connect, explain and predict, and achieve results.